SMA as means for sensitive biomedical sensors - Lindauer, Vojtěch; Váňová, Barbora; Rydlo, Pavel (Lékař a technika, 2021)
Shape memory alloys (SMA) are materials with specific electric, mechanic and thermal qualities originating in their microscopic structure and as such are used to design so-called Smart structures. In biomedicine, they are used mostly for their shape memory properties during intravasal surgery. The commonly used SMA material for biomedical purposes is Nitinol, a nickel-titanium alloy that exhibits, especially when annealed, among other properties also superelasticity and high resistivity with strain changes. This makes it suitable for usage in strain gauge sensors. In this work, NiTi annealed wires were used to create a strain gauge sensor, which exploits their unique properties. The properties of these sensors were then described using a climatic chamber, stretching device and a set of weights. Those properties were then compared to similar sensors, that are using different principles. The development, that followed, used these sensors in particular biomedical applications.
Keywords: biomedicínské technologie; Electronic Data Processing; chytré materiály; Manometry; Titanium; biomedicínský výzkum; slitiny s tvarovou pamětí; titan; Biomedical Research; kvantitativní vztahy mezi strukturou a aktivitou; Electric Impedance; Quantitative Structure-Activity Relationship; Shape Memory Alloys; elektrická impedance; Smart Materials; nikl; Nickel; Biomedical Technology; automatizované zpracování dat; manometrie